Limited Rationality and Endogenously Incomplete Contracts - Barton L. Lipman (Queen's University, Department of Economics, 1992)
The purpose of this paper is to provided a simple model in which limited rationality endogenously generates incomplete contracts. I model limited rationality as in Lipman [1991,1992], focusing on the idea that boundedly rational agents do not necessarily know every implication of their knowledge, but may, at a cost, compute these implications. This assumption implies the existence of subjective uncertainty in addition to the objective uncertainty the agents are contracting over. The presence of noncontractable subjective uncertainty can lead to contracts which are incomplete with respect to the contractable objective uncertainty. The most surprising result is that strategic bargaining over contracts can lead to incomplete contracts even with infinitesimal computation costs.
Keywords: 330